2011
DOI: 10.1002/adfm.201002171
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Tungsten Oxide: A Path Towards Dual Functionality Utilization for Efficient Anode and Cathode Interfacial Layers in Organic Light‐Emitting Diodes

Abstract: Here, we report on the dual functionality of tungsten oxide for application as an efficient electron and hole injection/transport layer in organic light‐emitting diodes (OLEDs). We demonstrate hybrid polymer light‐emitting diodes (Hy‐PLEDs), based on a polyfluorene copolymer, by inserting a very thin layer of a partially reduced tungsten oxide, WO2.5, at the polymer/Al cathode interface to serve as an electron injection and transport layer. Significantly improved current densities, luminances, and luminous eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 39 publications
1
63
0
2
Order By: Relevance
“…Nonetheless, the absence of the W +5 oxidation state on the air-exposed surface could be caused by tungsten reoxidation by air, not excluding oxygen vacancies from the material bulk. The characteristic defect states that lie within the band gap of these non-stoichiometric TMOs were also identified near the Fermi level [28,29,30], although in a minor degree for WO x (Fig. 2(d)).…”
Section: Properties Of Transition Metal Oxidesmentioning
confidence: 96%
See 2 more Smart Citations
“…Nonetheless, the absence of the W +5 oxidation state on the air-exposed surface could be caused by tungsten reoxidation by air, not excluding oxygen vacancies from the material bulk. The characteristic defect states that lie within the band gap of these non-stoichiometric TMOs were also identified near the Fermi level [28,29,30], although in a minor degree for WO x (Fig. 2(d)).…”
Section: Properties Of Transition Metal Oxidesmentioning
confidence: 96%
“…These results limit the oxide thickness on the final device to only a few nanometers and justifies the need for an ITO collecting electrode. Ultimately, actual conductivities will depend on the morphology of thermally-evaporated TMOs, which has been reported as completely amorphous for MoO x [20] and nano-crystalline for WO x [30]. Further study of preparation methods and post-deposition treatments could promote oxide crystallinity in order to enhance film conductivities.…”
Section: Properties Of Transition Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of the oxide reduction was monitored by measuring the intensity of the W 4f core levels and calculating the ratio between the W 6 þ component versus the W components with lower oxidation states (e.g., 5þ, 4þ). By depositing the first layers of the film (e.g., the first 7 nm) under H 2 environment it was found that they were sub-stoichiometric WO x (i.e., metallic [14]) with x¼2.5 and their refractive index equal to 3. Then the deposition ambient was switched to N 2 resulting in the deposition of a ca.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their high porosity these films exhibited refractive index depending on thickness (i.e., deposition time) varying between 2 for thinner films and 1.2 for thicker ones, within the visible range [12]. By switching the deposition ambient from N 2 to H 2 , sub-stoichiometric films, described as hwWO x with xo3, were also obtained, with their degree of stoichiometry (x) and refractive index depending on the exact H 2 partial pressure [13][14][15].…”
Section: Introductionmentioning
confidence: 99%